Table of Content - - (Journal of Curriculum and Teaching Methodology, 2023)
Table of Content: 1. The Effectiveness of Using Some Active Learning Strategies in the Developing of Rhetorical Skills Among First Grade Secondary Students in the Republic of Yemen Mr. Fouad Hussein Al-Salhi Ahmed 2. The Effect of Multiple Intelligences Based Teaching on the Achievement in the Social Studies Course and the Development of Critical Thinking Skills among the Ninth Grade Female Students in the United Arab Emirates Mrs. Raeda Sobhi Youssef Abdullah, Prof. Odeh Abdel-Gawad Abu Sneineh 3. Content Analysis of the Fourth Grade Mathematics Curriculum in Palestine in Light of Thinking Skills Dr. Ahmed M. Othman, Dr. Reem M. Jawabreh 4. The Impact of Using Prior and Acquired Knowledge Strategy on the Achievement and Acquisition of Scientific Concepts for the Third Basic Grade Students in Jordan Mrs. Fadia Hassan Nimr Abdel-Rahman, Prof. Ouda Abdel-Gawad Abu Sneineh 5. Teacher competencies necessary for teaching chemistry in the context of Twenty-first century skills Mr. Ahmad Mohammed Alamry , Co-Prof. Manal Hassan Bin Ibrahim 6. The Degree of Involving Seventh Grade Students in the Content of the English Language Textbook in Jordan Mr. Rami Mousa Al-Amayreh, Dr. Zuhair Dawood. Zaghlool 7. Computer teachers’ attitudes towards using Madrasati platform in teaching in Al-Makhwah Governorate Mr. Muteb Abduallh Muteb Alessi